2015
DOI: 10.1111/jdi.12452
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of dental pulp stem cells suppressed inflammation in sciatic nerves by promoting macrophage polarization towards anti‐inflammation phenotypes and ameliorated diabetic polyneuropathy

Abstract: Aims/IntroductionDental pulp stem cells (DPSCs) are thought to be an attractive candidate for cell therapy. We recently reported that the transplantation of DPSCs increased nerve conduction velocity and nerve blood flow in diabetic rats. In the present study, we investigated the immunomodulatory effects of DPSC transplantation on diabetic peripheral nerves.Materials and Methods DPSCs were isolated from the dental pulp of Sprague–Dawley rats and expanded in culture. Eight weeks after the streptozotocin injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 43 publications
7
72
0
1
Order By: Relevance
“…We have previously reported the therapeutic effect of DPSC transplantation on diabetic polyneuropathy. However, many of the engrafted DPSCs disappeared from the transplanted site during a certain period after transplantation, which is consistent with other cell transplantation therapies for ischemic heart disease and brain infarction.…”
Section: Discussionsupporting
confidence: 86%
“…We have previously reported the therapeutic effect of DPSC transplantation on diabetic polyneuropathy. However, many of the engrafted DPSCs disappeared from the transplanted site during a certain period after transplantation, which is consistent with other cell transplantation therapies for ischemic heart disease and brain infarction.…”
Section: Discussionsupporting
confidence: 86%
“…In an earlier study, intramuscularly transplanted MSCs improved sciatic nerve conduction velocity, sciatic nerve blood flow, and density of small vessels in the muscle of streptozotocin‐induced diabetic rats (Shibata et al, ). This was again recapitulated in other experiments, where several studies showed that transplantation of progenitor/stem cells, such as endothelial progenitor cells and MSCs, ameliorated neuropathy in experimentally‐induced diabetes (Jeong et al, ; Kim, Jin, & Bae, ; Omi et al, ). The therapeutic effects of MSCs not only depend on their differentiation capability to repair damaged tissue but also depend on their potency to activate endogenous progenitor cells, modulate local environment, and secrete various factors such as insulin‐like growth factor‐1, vascular endothelial growth factor (VEGF), and neurotrophin‐3 (Baraniak & McDevitt, ).…”
Section: Mscs Therapy In Cipn and Peripheral Neuropathysupporting
confidence: 53%
“…Therefore, inhibition of inflammatory cytokines has been considered as a useful target for CIPN prevention (Wolf, Gabay, Tal, Yirmiya, & Shavit, ). The modulatory action of MSCs on cytokine expression in peripheral tissues was previously demonstrated (Omi et al, ; Waterman et al, ). For example, treatment with MSCs reduced the levels of inflammatory markers such as NF‐κB p65, IL‐1β, TNF‐α, and IL‐6 in the sciatic nerve and spinal cord in experimental models of neuropathic pain (Al‐Massri et al, ; Gama et al, ).…”
Section: Mscs Therapy In Cipn and Peripheral Neuropathymentioning
confidence: 78%
See 1 more Smart Citation
“…Moreover, diabetic polyneuropathy, the most common microvascular complication of both type 1 and type 2 diabetes, involves inflammatory response during the disease development. DPSC introduction ameliorated diabetic polyneuropathy, improving the delay in sciatic nerve conduction velocities and the decreased nerve blood flow, through downregulating monocytes/macrophages, inflammatory messenger ribonucleic acid and upregulating CD206 mRNA (a M2 macrophage marker) [135].…”
Section: Experimental Therapeutic Applications Of Oral Mscs Inmentioning
confidence: 99%